Study on mixing anti-A monoclonal antibody and anti-B monoclonal antibody to make anti-AB save as abo blood grouping reagent - Trung, Nguyen Thi; Hai, Truong Nam (Vietnam Journal of Science and Technology, 2018)
So, it needs to balance the ratio of anti-A monoclonal antibody and anti-B monoclonal antibody  in the mixing so that the possibility of agglutination is the best. In this paper, anti-A monoclonal antibody (titer is 1/256) and anti-B monoclonal antibody (titer is 1/256) was used. The best results were obtained at one volume anti A monoclonal antibody is mixed one volume anti-B monoclonal antibody. The anti-A,B antibody titer was 1/128 for red blood group A and it was 1/128 for red blood group B. The intensity of agglutination reached  3+ for both red blood group A and B